Comparative genetic analysis of grayling (Thymallus spp. Salmonidae) across the paleohydrologically dynamic river drainages of the Altai-Sayan mountain region - Steven Weiss; Jacqueline Grimm; Duarte V. Gonçalves; Giulia Secci-Petretto; Gernot K. Englmaier; Mirgaliy Baimukanov; Elsa Froufe (Hydrobiologia, 2020)
A high number of grayling ( Thymallus ) species have been described from the Altai-Sayan mountain region, for which little to no genetic information is available. We investigated genetic relationships within this genus of salmonid fishes using mtDNA and microsatellite markers. The analysis focused on three putative species, Markakol grayling ( T. brevicephalus ), Upper Ob grayling ( T. nikolskyi ) and Mongolian grayling ( T. brevirostris ). We integrated these data with mtDNA sequences from eight other grayling species, including two of geographic proximity to the study area. Phylogenetic results revealed three pairs of reciprocally monophyletic sister species, two of which were phylogenetically juxtaposed across isolated drainage systems. Based on microsatellite analysis (up to 10 loci) no evidence of hybridization or introgression was found among species, supporting the mtDNA phylogeny. Based on a time-calibrated tree, divergence times between the focal taxa ranged from 0.36 to 1.1 MY. The genetic data support the distinction of these species and underscore the importance of paleohydrological dynamics in this biogeographically complex region. Well-documented mega-flood events in the region provide a model of how the contemporary cross-basin distribution of these species may have evolved.